Case Report: Exposure to Respirable Crystalline Silica and Respiratory Health Among Australian Mine Workers - Rumchev, Krassi; Hoang, Dong Van; Lee, Andy (Frontiers in Public Health, 2022)
Occupational exposure to respirable crystalline silica (RCS) is common in a range of industries, including mining, and has been associated with adverse health effects such as silicosis, lung cancer, and non-malignant respiratory diseases. This study used a large population database of 6563mine workers from Western Australia who were examined for personal exposure to RCS between 2001 and 2012. A standardized respiratory questionnaire was also administered to collect information related to their respiratory health. Logistic regression analyses were performed to ascertain the association between RCS concentrations and the prevalence of respiratory symptoms among mine workers. The estimated exposure levels of RCS (geometric mean 0.008mg/m3, GSD 4.151) declined over the study period (p <0.001) and were below the exposure standard of 0.05 mg/m3. Miners exposed to RCS had a significantly higher prevalence of phlegm (p=0.017) and any respiratory symptom (p=0.013), even at concentrations within the exposure limit. Miners are susceptible to adverse respiratory health effects at low levels of RCS exposure. More stringent prevention strategies are therefore recommended to protect mine workers from RCS exposures.